An Analysis of Economic Growth and Industrial Wastewater Pollution Relations in China - Yang, Hong; Zhou, Yuan; Abbaspour, Karim C (Consilience, 2010)
This paper investigates the relationship between the income growth and the trend in industrial wastewater discharge in China during the period 1981-2007. For the data encompassing all the provinces over the entire period considered, both an inverted U-shaped EKC and an N-shaped EKC are statistically significant. An analysis dividing provinces into rich and poor groups reveals that the EKC relations are mainly governed by the rich province group. The EKC relations for the poor province group are either not found or are statistically weak. A further analysis based on dividing the data into before and after the year 2000 is in favour of the quadratic EKC model. The results of this study show that the relationships between a given pollutant and income are temporal and spatial specific depending on the driving forces behind. This implies that results derived from one study for certain regions/countries and for a specific time period may not be generalized for other regions/countries and extrapolated to other periods.